Finline-integrated cold electron bolometer - Otto, E; Tarasov, M; Grimes, P; Kaurova, N; Kuusisto, H; Kuzmin, L; Yassin, G (2010)
The Cold-Electron Bolometer (CEB) is a sensitive millimetre-wave detector which is easy to integrate with superconducting planar circuits. CEB detectors have other important features such as high saturation power and very fast response. We have fabricated and tested CEB detectors integrated across the slot of a unilateral finline on a silicon substrate. Bolometers were fabricated using two fabrication methods: e-beam direct-write trilayer technology and an advanced shadow mask evaporation technique. The CEB performance was tested in a He3 sorption cryostat at a bath temperature of 280mK. DC I-V curves and temperature responses were measured in a current bias mode, and preliminary measurements of the optical response were made using an IMPATT diode operating at 110GHz. These tests were conducted by coupling power directly into the finline chip, without the use of waveguide or feedhorns. For the devices fabricated in standard direct-write technology, the bolometer dark electrical noise equivalent power is estimated to be about 5×10-16W/ √Hz, while the dark NEP value for the shadow mask evaporation technique devices is estimated to be as low as 3×10-17W/√Hz. © 2010 SPIE.